2020
DOI: 10.1007/s00421-020-04543-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of last lap speed in paced and maximal 1500-m time trials

Abstract: Purpose: The present study identified the physiological and performance characteristics that are deterministic during a maximal 1500-m time trial and in paced 1500-m time trials, with an all-out last lap. Methods: Thirtytwo trained middle-distance runners (n=21 male, VO2peak: 72.1±3.2; n=11, female, VO2peak: 61.2±3.7 mL•kg -1 •min -1 ) completed a 1500-m time trial in the fastest time possible (1500FAST) as well as a 1500MOD and 1500SLOW trial whereby mean speed was reduced during the 0-1100-m by 5% and 10%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 51 publications
3
36
1
Order By: Relevance
“…In contrast, middle-and long-distance track runners who perform their specific races at intensities above LT 2 commonly report lesser total training volumes with proportionally a smaller number of training sessions in zones 1 and 2, and more in zone 3 1 19 20 25 26 28 30 . This logic seems to be in line with recent studies that showed high participation of the anaerobic pathway in 800 m runners 54 and a high percentage of type II fibers in 1500 m runners 55 . Furthermore, studies that included middle-and long-distance runners have shown that longer events require greater total training volume, whereas shorter events require lower total training volume 25 30 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, middle-and long-distance track runners who perform their specific races at intensities above LT 2 commonly report lesser total training volumes with proportionally a smaller number of training sessions in zones 1 and 2, and more in zone 3 1 19 20 25 26 28 30 . This logic seems to be in line with recent studies that showed high participation of the anaerobic pathway in 800 m runners 54 and a high percentage of type II fibers in 1500 m runners 55 . Furthermore, studies that included middle-and long-distance runners have shown that longer events require greater total training volume, whereas shorter events require lower total training volume 25 30 .…”
Section: Discussionsupporting
confidence: 91%
“…Here, we present a method to estimate the proportion of skeletal muscle fiber types from frozen samples allowing for a larger number of samples to be measured in a standardized, cost, and labor-efficient way. Skeletal muscle fiber type distribution is a determinant of physical performance [ 27 30 ] and overall health [ 31 35 ] and is highly heritable in humans [ 11 , 12 ]. For example, a reduced proportion of oxidative slow-twitch type I fibers is associated with lower insulin sensitivity in the diabetic muscle [ 31 34 ] and muscle atrophy, e.g., age-related sarcopenia is progressing in a fiber type-specific manner [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…3). This implies a complex integration of muscular power, metabolic efficiency, biomechanical efficiency and fatigue resistance at the muscle fiber level, as well as an optimal pacing strategy [79,80].…”
Section: Mechanical Effectiveness: the Other Side Of The Middle-distance Coinmentioning
confidence: 99%
“…World-leading 5-10 km athletes run 120-200 km•week −1 [10,[62][63][64], while topclass marathon runners cover 150-250 km•week −1 [62][63][64]. Based on these running volume distinctions, one could argue that 1500-m runners in general are more long-distance than middle-distance athletes, although high finishing speed is required in slow races [80].…”
Section: Training Volumementioning
confidence: 99%